The lost thing : a tale for those who have more important things to pay attention to - Tan, Shaun (Sydney : Hachette Australia, 2008)
A boy finds a lost 'thing' on the beach where he's scavenging for his bottle top collection. The thing is a large, freakish creature that no one really notices. A quirky tale about finding your place in the world.
boek
Keywords: Tan, Shaun; Imagination -- Juvenile fiction; Fantasy -- Juvenile fiction; Lost and found possessions -- Fiction; Humorous stories